Prenatal treatment with methylazoxymethanol acetate as a neurodevelopmental disruption model of schizophrenia in mice. (15th May 2019) - Takahashi, Kohei; Nakagawasai, Osamu; Sakuma, Wakana; Nemoto, Wataru; Odaira, Takayo; Lin, Jia-Rong; Onogi, Hiroshi; Srivastava, Lalit K.; Tan-No, Koichi
Abstract: Methylazoxymethanol (MAM)-treated pregnant rat at gestation day (GD) 17 has been shown to be a valuable developmental animal model for schizophrenia. Yet, this model remains to be established in mice. In the present study, we examined behavioral, cytoarchitectural, and neurochemical changes in the offspring of MAM-treated mice and validated the model's face, construct and predictive validities. We found that in contrast to a single injection of MAM to dams at GD 15, 16 or 17, its daily administration from GD 15 to 17 led to deficits in prepulse inhibition (PPI) of startle in the post-pubertal offspring. In addition, we observed behavioral deficits in working memory and social interactions, as well as an increase in locomotor activity induced by the NMDA antagonist MK-801 in GD15-17 MAM offspring. These animals also showed a reduction in the volume of the prefrontal cortex (PFC) and hippocampus, neuroanatomical changes such as discontinuities and heterotopias in the hippocampus, and an increase of DA level and DOPAC/DA ratio in the medial PFC. Atypical antipsychotic drugs clozapine, risperidone, and aripiprazole, but not the typical drug haloperidol, reversed the deficit in PPI and social withdrawal in the offspring of MAM-treated dams. In contrast, MK-801-induced hyperactivity in MAM mice was reversed by both and typical or atypical antipsychotic drugs. Taken together, the treatment of pregnant mice with MAM during GD 15–17 offers a new approach to study neurobiological mechanisms involved in the pathogenesis of schizophrenia. Highlights: MAM mice showed schizophrenia-like behaviors. MAM mice exhibited neuroanatomical changes in the hippocampus. DA concentrations and DOPAC/DA increased in the mPFC of MAM treated mice. MAM-induced PPI deficits and social withdrawal improved with atypical antipsychotics. Atypical and typical antipsychotics improved hyperactivity by MK-801 in MAM mice.